Baicalein Loaded Polysorbate 80 Nanostructured Lipid Carriers Offered Enhanced Stability and In Vitro Drug Release - Kaushik, Dinesh (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this work was to characterize baicalein loaded nanostructured lipid carriers (NLCs) intended for brain targeting by intravenous route of administration. Materials and Methods: The NLC system, composed of stearic acid and polysorbate 80, was characterized in terms of its physicochemical properties, differential scanning calorimetry (DSC), and in vitro drug release. Results and Discussion: The lipid nanoparticles were spherical with an average size of ∼100 nm. The zeta potential of the nanoparticles was about −50 mV. DSC studies suggested that the majority of the inner cores of polysorbate 80 NLCs had a slightly disordered crystal arrangement. The nanoparticulate dispersions demonstrated good physical stability during storage for 6 days. Conclusion: Polysorbate 80 NLCs improved baicalein’s stability and the ability of baicalein to penetrate the brain; thus, this is a promising drug-targeting system for the treatment of central nervous system.